The institutionalisation of childhood and the institutionalisation of education. Reconsidering a not so simple relationship - Sascha Neumann (Social Work and Society)
In social sciences, the notion of institutionalisation of childhood is well established as a concept for theorizing childhood and analysing the social position of children in modern societies. Among scholars, there is broad agreement that the institutionalisation of education, especially scholarisation, makes up a major part of the institutionalisation of childhood. Assuming that both processes of institutionalisation are entangled, this paper will, nonetheless, argue, that they should not be confused with each other. Otherwise, it would not possible to study how these processes are related and interfere. In a first step, it will be illustrated in how far the institutionalisation of childhood can systematically and analytically be distinguished from the notion of the institutionalisation of education. In a second step, the relationship of both processes will be further clarified by referring to empirical findings and data of two research projects. Besides the interference, the two examples demonstrate as well the different theoretical conclusions which both perspectives suggest.